Comparative Study of the Use of Different Biomass Bottom Ash in the Manufacture of Ceramic Bricks - Eliche-Quesada, D; Felipe Sesé, Manuel Ángel; Martínez-Martínez, S; Pérez-Villarejo, Luis (Journal of Materials in Civil Engineering, 2018)
The present study evaluates the suitability of several types of biomass bottom ashes [wood bottom ash (WBA), pine-olive pruning bottom ash (POPBA), olive stone bottom ash (OSBA), and olive pomace bottom ash (OPBA)] as an alternative source to replace ceramic raw material in the production of clay bricks. The clay and biomass bottom ash were characterized by means of X-ray diffraction (XRD) (crystallinity), X-ray fluorescence spectroscopy (XRF) (chemical composition), carbon, nitrogen, hydrogen, and sulphur (CNHS) (elemental chemical analysis), and particle-size distribution. The specimens were manufactured by mixing clay and 20 by weight (wt%) of biomass bottom ash, subsequently compacted and fired at 1,000°C. The fired samples were characterized to determine their technological properties. The results indicate that brick formulations containing biomass bottom ash decreased the bulk density of the control bricks. At the same time, they have suitable mechanical behavior. In addition, thermal properties of clay-biomass bottom ash are manifestly better than those of the clay control bricks. The heavy-metal concentration in the leaching test of the bottom ash-clay bricks establishes that the bricks do not present environmental problems.
Keywords: biomass bottom ash reuse; sustainable clay bricks; physical; mechanical and thermal properties; Scopus; JCR